ANALISIS SENTIMEN OPINI PUBLIK BAHASA INDONESIA TERHADAP WISATA TMII MENGGUNAKAN NAÏVE BAYES DAN PSO - Ratih Yulia Hayuningtyas; Retno Sari (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2019)
Sentiment analysis is a text analysis to identify an opinion. Public opinion or reviews are important for visitors who will travel to tourist because of the reviews will produce information about the destination. One of the tourist attractions in Indonesia that Taman Mini Indonesia Indah one of the tourist attractions that has extraordinary. Reviews about Taman Mini Indonesia Indah make it difficult for visitors to draw conclusions about information about Taman Mini Indonesia Indah. Therefore a classification method in study with Naïve Bayes and PSO methods. In study using data as many 50 positive reviews and 50 negative reviews where the results of accuracy obtained using the Naïve Bayes method of 70% while the accuracy of using Naïve Bayes and PSO is 94,02%.